2009
DOI: 10.1007/s11552-009-9223-6
|View full text |Cite
|
Sign up to set email alerts
|

Free Muscle Transfer in Posttraumatic Plexopathies Part II: The Elbow

Abstract: The indications for free muscle transfer in brachial plexopathies are prolonged denervation time or inadequate upper extremity function after primary nerve reconstruction. The purpose of this study is to analyze the outcomes of free muscle transfer for elbow flexion and extension in brachial plexopathies in relation to the different muscles used and the respective motor donors. Seventy-three muscles were transferred for elbow flexion and ten for elbow extension. Latissimus dorsi (LD) was used in 37 cases, grac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
14
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…In case of complete elbow flexion palsy, pectoralis major transfer [24] could be an interesting solution. Finally, several free and reinnervated muscle transfers were proposed including gracilis [25][26][27][28][29] and rectus femoris [25,27]. While some series give encouraging results with 79% of M4 quoted strength [28], others show overall grade inferior to M3 [27] and a failure rate reaching 15% [29].…”
Section: Discussionmentioning
confidence: 99%
“…In case of complete elbow flexion palsy, pectoralis major transfer [24] could be an interesting solution. Finally, several free and reinnervated muscle transfers were proposed including gracilis [25][26][27][28][29] and rectus femoris [25,27]. While some series give encouraging results with 79% of M4 quoted strength [28], others show overall grade inferior to M3 [27] and a failure rate reaching 15% [29].…”
Section: Discussionmentioning
confidence: 99%
“…In 53% of the described cohort of 34 patients, classic reconstructive techniques restored sufficient hand/arm function similar to that reported in the literature. 37,38 In the remaining 47%, the patients demonstrated dismal hand function attributable to poor or inadequate surgical management or extensive neural injury. For this patient group In ARAT, a maximum of 57 points is attainable.…”
Section: Discussionmentioning
confidence: 99%
“…sions, repair has been focused on restoration of shoulder stability and biceps function. 35,36,38 If the lower roots are avulsed, however, the return of hand function is hardly ever achieved due to limited axonal support, long denervation time of muscles located more distally, and accompanying joint stiffness. Even though bodily integrity is maintained, some patients refer to their hand as an insensate, useless appendage that they would rather have amputated.…”
mentioning
confidence: 99%
“…However, ethnic differences in the strength of the gracilis muscle may exist. Terzis and Kostopoulos [19] reported that the gracilis strength was inadequate to allow for sufficient elbow flexion in Caucasians, whereas, in studies on East Asians, using the gracilis muscle provided good results [16]. This discrepancy may be attributed to variations in body size between Caucasians and East Asians.…”
Section: Discussionmentioning
confidence: 99%